2000
DOI: 10.1097/00003226-200007000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Corneas of Diabetic Patients

Abstract: The aggregates of wide-spaced collagen fibrils, which have not been described in other basement membranes of diabetic patients, may reflect an excessive glycosylation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 32 publications
3
64
0
1
Order By: Relevance
“…The uncontrolled impairment of corneal wound healing increases the susceptibility of corneal ulcer, microbial keratitis, and even perforation. Diabetic corneal pathology always exhibits epithelial basement membrane abnormalities, reduced hemidesmosome density, and delayed wound healing (3,4). However, hyperglycemia also directly impairs the cellular metabolism and causes abnormal changes of corneal epithelium, such as Akt-, epidermal growth factor receptor (EGFR)-, and Sirt1-mediated cell responses to environmental challenges (5)(6)(7).…”
mentioning
confidence: 99%
“…The uncontrolled impairment of corneal wound healing increases the susceptibility of corneal ulcer, microbial keratitis, and even perforation. Diabetic corneal pathology always exhibits epithelial basement membrane abnormalities, reduced hemidesmosome density, and delayed wound healing (3,4). However, hyperglycemia also directly impairs the cellular metabolism and causes abnormal changes of corneal epithelium, such as Akt-, epidermal growth factor receptor (EGFR)-, and Sirt1-mediated cell responses to environmental challenges (5)(6)(7).…”
mentioning
confidence: 99%
“…30 Some studies with fluorophotometry show that this barrier function is weakened in DM leading to an increase in permeability to fluorescein. 30,31 The corneal epithelium in patients with DM exhibits alterations in both cellular components and basal membrane, which could impair the physiology of the corneal epithelial barrier function 32 and cause the cornea to be more vulnerable to foreign pathogens, such as bacteria and fungi.…”
Section: Tear Filmmentioning
confidence: 99%
“…32 Although the cause of theses abnormalities is not clear, some studies suggested that these disorders may be due to altered basal membrane structure and/or epithelial integrin expression, 28,31 increased glycosylation of type IV collagen 32 and fibronectin, abnormal regulation of the synthesis of extracellular matrix, increased IV collagen, and decreased laminin 31 and heparin sulfate. 27 As far as epithelial basal membrane alteration is concerned, people with DM show an accumulation of fibrillar and granular material between the epithelial cells and Bowman's membrane, thickening and multilayering of the basal membrane, 32,33 and accumulation of glycation end products (AGEs). 34 Despite this, Quadrado et al 29 found that basal membrane in DM was lower in density compared with healthy subjects, and they suggested that this could be result of a combination of different mechanisms, such as decreased innervation at the subbasal nerve plexus, basal membrane alterations, and higher turnover rate in basal epithelial cells.…”
Section: Tear Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…well as abnormalities of the corneal epithelial basement membrane [2,3] have also been described in humans or animals with diabetes. The cornea of individuals with diabetes could seem normal until the corneal surface is damaged, when a delay in epithelial healing becomes apparent.…”
mentioning
confidence: 97%